Correlação da morfometria e da compactação da cromatina de espermatozóides de touro Zebuíno sobre a taxa de clivagem e formação de blastocistos em programas de produção "IN VITRO" - Silva, Ricardo Tomaz da (2006)
38 PIVs carried through in two laboratories of the Uberaba MGBRASIL had been used in this work with the objective to evaluate the relationship between condensation chromatin and head morphometry of spermatozoa and cleavages and blastocyst formation rates using semen of zebu bulls with normal routine tests of fertility. Smears of semen stained with of Toluidine Blue and computer image analysis had been used to evaluate the morphometry and chromatin condensation. Area (A), perimeter (P), width (L), length (C), width:length ratio (L/C), ellipticity (E), shape factor (FF), side symmetry (SL), anterior-posterior symmetry (SAP) and the three first Fourier values (F0, F1, F2) had been evaluated in the morphometric analysis. The chromatin was evaluated in relation to intensity of condensation and homogeneity. The results allowed concluding that the influence of light variations in the sperm head morphometry and the chromatin condensation on the cleavage and number of normal morfologic blastocyst in the PIV is small.